Cell formation problem: a genetic algorithm based on an inter-operation flow matrix - Xambre, A. R. (2015)
When designing a Cellular Manufacturing System an essential step is to solve the cell formation problem: determining which machines and parts belong to each cell. The main purpose is to obtain autonomous cells capable of completely processing the respective family of parts and thus eliminate, or at least reduce, intercellular flow. Additionally, if there is more than one machine of each type (i.e. if a certain operation can be performed in different machines) the assignment of operations to specific machines becomes part of the cell formation problem. In this paper an algorithm for the cell formation problem with multiple identical machines, which minimises the intercellular flow, is presented. The algorithm uses the information provided by an inter-operation flow matrix so the real flow, associated with each solution, can be adequately determined. Furthermore, due to the combinatorial nature of this problem, the procedure is based on genetic algorithms in order to improve the exploration of the solution space.